Establishment of Insulin-Producing Cells From Human Embryonic Stem Cells Underhypoxic Condition for Cell Based Therapy - Rattananinsruang, Piyaporn; Dechsukhum, Chavaboon; Leeanansaksiri, Wilairat (Frontiers in Cell and Developmental Biology, 2018)
Diabetes mellitus is a group of diseases characterized by abnormally high levels of glucose in the blood stream. In developing a potential therapy for diabetic patients, pancreatic cells transplantation has drawn great attention. However, the hinder of cell transplantation for diabetes treatment is insufficient sources of insulin-producing cells. Therefore, new cell based therapy need to be developed. In this regard, human embryonic stem cells (hESCs) may serve as good candidates for this based on their capability of differentiation into various cell types. In this study, we designed a new differentiation protocol that can generate hESC-derived insulin-producing cells (hES-DIPCs) in a hypoxic condition. We also emphasized on the induction of definitive endoderm during embryoid bodies (EBs) formation. After induction of hESCs differentiation into insulin-producing cells, the cells obtained from the cultures exhibited pancreas-related genes such as Pdx1, Ngn3, Nkx6.1, GLUT2 and insulin. These cells also showed positive for DTZ-stained cellular clusters and contained ability of insulin secretion in a glucose-dependent manner. After achievement to generated functional hES-DIPCs in vitro, some of the hES-DIPCs were then encapsulated named encapsulated hES-DIPCs. The data showed that the encapsulated cells could possess the function of insulin secretion in a time-dependent manner. The hES-DIPCs and encapsulated hES-DIPCs were then separately transplanted into STZ-induced diabetic mice. The findings showed the significant blood glucose levels regulation capacity and declination of IL-1β concentration in all transplanted mice. These results indicated that both hES-DIPCs and encapsulated hES-DIPCs contained the ability to sustain hyperglycemia condition as well as decrease inflammatory cytokine level in vivo. The findings of this study may apply for generation of a large number of hES-DIPCs in vitro. In addition, the implication of this work is therapeutic value in type I diabetes treatment in the future. The application for type II diabetes treatment remain to be investigated.